2011
DOI: 10.3892/ol.2011.316
|View full text |Cite
|
Sign up to set email alerts
|

The role of components of the chromatin modification machinery in carcinogenesis of clear cell carcinoma of the ovary (Review)

Abstract: Abstract. Recent data have provided information regarding the profiles of clear cell carcinoma of the ovary (CCC) with adenine-thymine rich interactive domain 1A (ARID1A) mutations. The purpose of this review was to summarize current knowledge regarding the molecular mechanisms involved in CCC tumorigenesis and to describe the central role played by the aberrant chromatin remodeling. The present article reviews the English-language literature for biochemical studies on the ARID1A mutation and chromatin remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…In our study, we observed that ARID1A duplication in patient-derived fibroblasts slowed cell-cycle progression from G1 to S phase (Figure 4). This result was consistent with the expected role of ARID1A in the cellcycle checkpoint machinery 20 and with the body of oncological literature showing that the overexpression of ARID1A leads to an arrest of cell-cycle progression in G1/S phase. 21 Interestingly, it has been demonstrated that the BAF complex is involved in the proliferation and differentiation of neural stem and progenitor cells.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we observed that ARID1A duplication in patient-derived fibroblasts slowed cell-cycle progression from G1 to S phase (Figure 4). This result was consistent with the expected role of ARID1A in the cellcycle checkpoint machinery 20 and with the body of oncological literature showing that the overexpression of ARID1A leads to an arrest of cell-cycle progression in G1/S phase. 21 Interestingly, it has been demonstrated that the BAF complex is involved in the proliferation and differentiation of neural stem and progenitor cells.…”
Section: Discussionsupporting
confidence: 92%
“…Regulation of ARID1A in apoptosis evasion remains unclear but may involve inhibition of Fas‐mediated cell death, which was suggested by a previous study showing that suppression of ARID1A by short hairpin RNA inhibited both Fas‐Ab‐induced caspase‐8 cleavage and mitochondrial potential reduction (35). Moreover, there is evidence demonstrating that ARID1A mutation caused dysfunction of histone H2B ubiquitination and restoration of nuclear histone H2B resulted in an aberration of chromatin remodeling proteins, which led to apoptosis evasion (36).…”
Section: Discussionmentioning
confidence: 99%
“…In human tumors, ARID1A was found mutated or missing frequently in carcinomas of the breast, ovarian, lung and kidney in several recent reports [49-51]. Comprehensive molecular studies revealed that ARID1A mutations exist in 3% of ccRCC [52]. But recent articles show that 12% mRNA mutation in genomic alterations (GAs) [10] and 51% protein loss of ARID1A [13] in ccRCC.…”
Section: Discussionmentioning
confidence: 99%